1968
DOI: 10.1017/s0074180900019240
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Astronomical Observations for Studying Continental Drift, Polar Motion, and the Rotation of the Earth

Abstract: The analysis of 66 years of concurrent latitude observations of the ILS shows that the mean pole has a secular motion which consists of a progressive component of about 0′′.0035/yr (10 cm/yr) along the meridian 65°W and a librational component (oscillation) of 24-year period along the meridian 122°W (or 58°E). Crustal displacements in latitude are not found within the errors of observation, about 1 cm/yr.Comparable, concurrent observations for time (longitude) have not been made but programs are being organize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

1975
1975
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 1 publication
0
13
0
Order By: Relevance
“…The Markowitz wobble is a somewhat irregular polar motion with a magnitude of roughly 20 to 50 milliarcseconds (mas) (Markowitz 1960(Markowitz , 1968. Until recently, the existence of this oscillation was in doubt for several reasons, including changes in the star catalogues and modifications in data processing techniques (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The Markowitz wobble is a somewhat irregular polar motion with a magnitude of roughly 20 to 50 milliarcseconds (mas) (Markowitz 1960(Markowitz , 1968. Until recently, the existence of this oscillation was in doubt for several reasons, including changes in the star catalogues and modifications in data processing techniques (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…With such a data set, it is possible to evaluate the trend in polar motion and to investigate possible low-frequency periodic motions, which have been suggested previously (Hattori 1959;Markowitz 1960Markowitz , 1968Markowitz , 1970. Early investigations, which used optical astronomical data, were plagued by the possibility of systematic errors in the proper motions contained in the star 1920 1940 1960 1980 2000 1900 1920 1940 1960 1980 2000 (1988) concluded that the low-frequency oscillation was caused by systematic effects a t the individual stations.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the nature of the very low-frequency polar motion, it is necessary to assemble a series of polar-motion observations that are consistent within one reference system. With such a data set, it is possible to evaluate the trend in polar motion and to investigate possible low-frequency periodic motions, which have been suggested previously (Hattori 1959;Markowitz 1960Markowitz , 1968Markowitz , 1970. Early investigations, which used optical astronomical data, were plagued by the possibility of systematic errors in the proper motions contained in the star 1920 1940 1960 1980 2000 1900 1920 1940 1960 1980 2000 catalogues and by the fact that some of the ILS stations did not observe continuously [see Yumi & Wako (1965) and Lambeck ( 1 980,].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Adhikari and Ivins (2016) demonstrated that the continent-ocean mass transport and the terrestrial water storage can explain the observed polar motion departure from a secular trend (excited by GIA) since 2000. Nevertheless, these obviously do not well explain the majority of the decadal polar motion, including the ∼30 year Markowitz wobble (e.g., Gross, 2015;Markowitz, 1968;Schuh et al, 2001;Vicente & Wilson, 2002). In addition, Chao (2017) in his recent studies asserted two rotational modes in the Earth system, namely, the axial torsional libration and the inner core wobble, owing to the mantle-inner core gravitational torques (Buffett, 1996).…”
Section: Introductionmentioning
confidence: 99%